Labour Markets, Flexible Specialization and the New Microcorporatism The Case of Canada’s Major Appliance Industry - Wells, Don (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2001)
Summary“High performance” management systems in unionized workplaces have the potential to create a more microcorporatist industrial relations system in Canada. Increasing interfirm and intrafirm competitiveness, combined with restratification of internal and external labour markets, promote a deepening of “core” workforce dependency on employers. Microcorporatist tendencies reflect more active worker cooperation in achieving management productivity, quality and flexibility goals. Analysis of development of these tendencies in the major appliance industry suggests that microcorporatism has contradictory implications. In one direction lies the displacement of both “social movement” unionism and social democratic labour politics by a local-centred unionism that is increasingly captured by the logic of market competition. In a second direction lies a logic of greater worker resistance related to increased worker control of labour processes.